Cancer Immunotherapy and the Immune Response in Follicular Lymphoma - Stenner, Frank; Renner, Christoph (Frontiers in Oncology, 2018)
Follicular lymphoma is the most frequent indolent lymphoma in the Western world and is characterized in almost all cases by the t(14;18) translocation that results in overexpression of BCL2, an anti-apoptotic protein. The entity includes a spectrum of sub-entities which differ from an indolent to a very aggressive growth pattern. As a consequence, treatment can include watch & wait up to intensive chemotherapy including allogeneic stem cell transplantation. The immune cell microenvironment has been recognised as a major driver of outcome of follicular lymphoma patients and gene expression profiling has identified a clinically relevant gene expression signature that classifies an immune response to the lymphoma cells. It is known for some time that the immune cell composition of the lymphoma microenvironment is important because high numbers of tissue-infiltrating macrophages correlate with poor outcome in patients receiving chemotherapy but not in patients receiving the combination of chemotherapy and CD20-specific monoclonal antibody rituximab. In addition, TCR signaling of tumor infiltrating lymphocytes are dysfunctional leading to an impaired capacity to form an intact immunologic synapse. Approaches restoring local T cell function, e.g. by usage of check-point inhibitors has demonstrated clinical activity (ORR 40%) and can achieve long term remissions. Ongoing trials with re-programed autologous CAR-T cells achieve response rates in approx. 50% of follicular lymphoma patients with relapsed and even refractory disease. Responses lasting for more than 6 months might be durable, indicative for a successful restoration of a functional immune system. In summary, follicular lymphoma is a malignant disease where the control by the immune system ultimately decides about progression and transformation rate. The advent of monoclonal antibodies has changed the way we treat follicular lymphoma and new approaches restoring the individual immune control will hopefully improve results further.